DESIGN INTERFACE BETWEEN SECURITY SYSTEM SENSOR INFRA RED ROOM WITH PC-BASED - Candra Trisurgo; Eko Hadiyanto, SSi, MM (Jurnal Sistem Komputer, 2001)
At this writing discusses the interface design of safety systems use a room with a PC- based infrared sensors. The design of this interface is made in order to read data from outside the computer and translates the data, so data were initially still shaped analog data with a logic high (1) and low (0). The sensors used to detect the state of the room, if there is an entrance to the room. Such circumstances it is done continuously with rocks control program that monitors and instantly displays the state of the motor drive if you get the data from the sensors. With this design, is expected to facilitate or as a means of support to enhance system security. Use of this design was made in order to detect the condition in some rooms as well as making it easier for the security unit to anticipate and take priority.